Towards inclusive and accessible e-learning in gauteng classrooms: An ICT integration framework for South African schools - Mwale, Bongani June; Nyamkure, Blondel; Maluleke, Raymond Nkateko (Global Journal of Social Sciences Studies, 2025)
South Africa has attempted to enhance its education system. It has achieved this by employing information and communication technology (ICT) to bridge the digital divide and enhance educational outcomes. Despite substantial government investment in e-learning, particularly in Gauteng township schools, its use remains inequitable, and classrooms lack true accessibility and inclusivity. This study examines the barriers to ICT implementation in schools, evaluates the effectiveness of existing e-learning approaches, and proposes strategies to enhance the accessibility and inclusivity of ICT. The study conceptualises an ICT integration model, emphasising equity-centred access, teacher agency, learner-centric design, and the promotion of communicative engagement. The study employs a mixed-methods approach that incorporates desktop and systems reviews, informed by an ethnographic perspective. Qualitative data was collected through interviews, analysed through coding and thematic analysis and quantitative data through semi-structured questionnaires and analysed through regression analysis. The study noted that numerous factors influence the accessibility of e-learning in educational institutions, such as policy goals, infrastructure investment, and ict strategy implementation. The results also observed that there are still educators' pedagogical training challenges that need to be addressed and there is a need for investments in more educational resources: ict tablets and connectivity to enhance access of educational materials to learners and educators. The study recommends that there should be increased ict resources support to schools by the Department of Education and training on pedagogy and educator change management to ensure that there is successful ict utilisation in the classroom.